MicroRNA miR-8 promotes cell growth of corpus allatum and juvenile hormone biosynthesis independent of insulin/IGF signaling in Drosophila melanogaster. (September 2021) - Zhang, Jie; Wen, Di; Li, Emma Yiyang; Palli, Subba Reddy; Li, Sheng; Wang, Jian; Liu, Suning
Abstract: The Drosophila melanogaster corpus allatum (CA) produces and releases three types of sesquiterpenoid hormones, including juvenile hormone III bisepoxide (JHB3), juvenile hormone III (JH III), and methyl farnesoate (MF). JH biosynthesis involves multiple discrete enzymatic reactions and is subjected to a comprehensive regulatory network including microRNAs (miRNAs). Using a high throughput sequencing approach, we have identified abundant miRNAs in the D. melanogaster ring gland, which consists of the CA, prothoracic gland, and corpus cardiaca. Genetic and qPCR screens were then performed in an attempt to uncover the full repertoire of CA miRNAs that are involved in regulating metamorphosis. miR-8 was identified as a potential candidate and further studied for its role in the CA. Overexpression of miR-8 in the CA increased cell size of the gland and expression of Jhamt (a gene coding for a key regulatory enzyme in JH biosynthesis), resulting in pupal lethality. By contrast, sponge-mediated reduction of miR-8 in the CA decreased cell size and Jhamt expression, but did not cause lethality. Further investigation revealed that miR-8 promotes cell growth independent of insulin/IGF signaling. Taken together, these experiments show that miR-8 is highly expressed in the CA and exerts its positive effects on cell growth and JH biosynthesis. The miRNAs data in the ring gland also provide a useful resource to study how miRNAs collaboratively regulate hormone synthesis in D. melanogaster . Graphical abstract: Image 1 Highlights: A high throughput sequencing identifies multiple miRNAs in the Drosophila melanogaster ring gland. A two-tiered screen of miRNAs reveals that miR-8 in the corpus allatum (CA) is required for metamorphosis. miR-8 promotes CA cell growth and JH biosynthesis independent of IIS/TOR.